PENGEMBANGAN MEDIA PEMBELAJARAN ULATIK (ULAR TANGGA OPTIK) UNTUK MENGUKUR KETERAMPILAN PROSES SAINS DAN SISWA KELAS XI SMA MUHAMMADIYAH 1 PONTIANAK - Lia Wahyuningsih Budiarti; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
This research is development research that aims to find out students' science process skills in physics subjects related to optical material for class XI SMA Muhammadiyah 1 Pontianak. Aspects of skills that are measured are observing, communicating, classifying, predicting, and concluding. Where science process skills are measured after being given learning with the media of ulatik (optical snake ladder) physics. It was found that the ulatik media could measure students' science process skills well. Where the instrument used has been validated by a material expert with a feasible criterion of 80%. In addition, the learning tools in the form of lesson plans used also obtained an average of 3.27 with a very suitable category for use.